An Analysis of Mathematics Education Students Errors in Solving PISA Adaptation Test - Kurniati MA, Ratnah; Sugiarto, Sigit; Nurwahidah, Nurwahidah; Nur, Ismail M. (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2024)
The objectives of this research are to determine the errors of mathematics education students in solving the PISA adaptation test. This research is an exploratory study with a qualitative approach that will produce descriptive data in the form of a description of the types and locations of student errors in solving PISA 2022. The subjects in this study were six students of the Program Studi Pendidikan Matematika Program Studi Diluar Kampus Utama (PSDKU) at Pattimura University in Maluku Barat Daya. They were in the second, fourth, and sixth semesters. Five students from each semester were asked to solve a question on the PISA adaptation test level 6, the highest level of the PISA test, as the method for selecting the subject. Six subjects were selected as research subjects out of the 15 who took the test. The conclusions in this study are that the ability of subjects to solve the PISA adaptation test is still very low. Only 3 out of 15 students can answer and provide the right solution for the test, and only 6 out of 15 students can figure out what to do to solve PISA adaptation test level 6. However, among the six students who gave their answers to this problem, there are some who have conceptual errors in the topic of SPLDV (System of Linear Equations with Two Variables). Besides conceptual errors, researchers also found that there is a subject who is incorrect in solving basic arithmetic operations involving parentheses